A new solar combined cycle integrated with heat pump system. (5th June 2020) - Razi, Faran; Dincer, Ibrahim
Highlights: Development of a novel solar based combined cycle integrated with heat pump system. Proton Exchange Membrane electrolyzer for hydrogen production. Overall system energy and exergy efficiencies of 52% and 42% respectively. Gas turbine cycle producing 50 MW power and steam turbine cycle generating 3250 kW. Abstract: This paper develops and studies a solar combined cycle system that is integrated with a solar-assisted heat pump for providing electrical power, space-heating, space-cooling, hydrogen, and hot water. Thermodynamic analysis through exergy as well as energy approaches is employed for assessment and evaluation of the overall performance of the system. The proposed system is also assessed by performing parametric studies for observing the impact of several factors on the overall performance of the system. The results of this study show that the energy efficiency of the multi-generation system is 52% while the exergy efficiency is evaluated to be 42%. Moreover, hydrogen is produced at a rate of 0.51 kg/h while the power outputs from the gas turbine and steam turbines are 50 MW and 3.25 MW respectively.